A New 3D 10-Connected Cd(II) Based MOF With Mixed Ligands: A Dual Photoluminescent Sensor for Nitroaroamatics and Ferric Ion - Wang, Jun; Wu, Jian; Lu, Lu; Xu, Hongjia; Trivedi, Manoj; Kumar, Abhinav; Liu, Jianqiang; Zheng, Mingbin (Frontiers in Chemistry, 2019)
The precise unification of functional groups and photoluminescence properties can deliver metal-organic frameworks (MOFs) with multifarious applications like selective detection of nitroaromatic compounds (NACs) an important ingredient of explosive as well as cation and anion sensing. Hence, a new 3D metal-organic framework (MOF) [Cd2(btc)(bib)(COO)(H2O)•H2O]n (1) has been synthesized using mixed ligand strategy by solvothermal reaction of cadmium acetate dihydrate with two ligands viz. 1,3,5-benzenetricarboxylic acid (H3btc) and 1,4-bis(2-methyl-imidazol-1-yl)butane (bib) and structurally characterized. The MOF 1 possesses highly 10-connected network which is based on {Cd4(btc)2(bib)4}molecular building block. The sensing studies indicated that 1 could be the fluorescent sensor for sensitive recognition of NACs in particular 2,4,6-trinitrophenol (TNP) with notable quenching (Ksv = 5.42 × 104 Mˉ1) and low limit of detection with 1.77 ppm. Additionally, 1 also displayed selective sensing for Fe3+ ions with Ksv = 6.05 × 103 Mˉ1 and LOD = 1.56 ppm. Also, this dual sensor displayed excellent reusability towards the detection of TNP and Fe3+ ion. Theoretical calculations have been performed to propose the probable mechanism for the decline in the luminescence intensity of the MOF when NACs are added to it. Calculations indicated that because of the charge transfer and weak interaction that is operating between NACs and MOF the decline in the photoluminescence intensity resulted.